Capsule endoscopy – not just for the small bowel: a review. (January 2014) - Parker, Clare Elizabeth; Spada, Christiano; McAlindon, Mark; Davison, Carolyn; Panter, Simon
<x xml:space="preserve">Abstract</x> Video capsule endoscopy is being increasingly used to investigate the esophagus and colon as well as the small bowel. With the advancement of technology used in capsule endoscopy there have been marked improvements in diagnostic rates for colon capsule endoscopy in the detection of colonic polyps and colorectal cancer. It is also being increasingly used in the field if inflammatory bowel disease to investigate for mucosal inflammation and could potentially be used to assess mucosal healing. It also has role in completing the evaluation of colonic pathology in those in whom colonoscopy is incomplete. Esophageal capsule is preferred by patients over esophagogastroduodenoscopy (EGD) but as yet does not rival EGD in terms of diagnostic accuracy however the advent of magnetically steerable capsules may improve this. This review covers advances in the field of colon and esophageal capsule endoscopy; it covers diagnostic capabilities of these 2 tools as well as technical aspects of both procedures and preparation.